Isolated anorectal malformation with rectoperineal fistula in monozygotic twins - Yuki Muta; Akio Odaka; Seiichiro Inoue; Yoshifumi Beck (Elsevier, 2019)
Incidence of anorectal malformation (ARM) is reportedly 1 in approximately 2500-5000 live births. While its etiology remains elusive, most evidence indicates genetic factors to be the major cause. One-third of all ARM cases are isolated, whereas the others are a part of other anomalies (syndromic). Herein, we report a case of low-level ARM with anocutaneous fistula in monozygotic twins. Male monozygotic twins (birth weight, 3036 and 2706 g, respectively) were born to a 31-year-old woman at gestational week 36. The twins' physical examination revealed imperforated anus with anocutaneous fistula. Anterior sagittal anorectoplasty (ASARP) was performed when the twins were 2 years old. The postoperative course was uneventful, and their postoperative anal functions were satisfactory. No other complications were noted. ARM in monozygotic twins is rare. Reports on familial ARM will help clarify the pathogenesis of ARM and other congenital diseases. Keywords: Anorectal malformation, Monozygotic twins, Fistula